2007
DOI: 10.1016/j.rmed.2007.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium suppresses acetylcholine-induced release of chemotactic mediators in vitro

Abstract: The driving force in the progression of COPD is the development of exacerbations which are mostly the result of excessive inflammation. Bronchodilatators play an important role in the treatment of COPD. The reported reduction in exacerbation rates in COPD is due to the inhibition of vagal-mediated bronchoconstriction and mucus secretion. However, recent studies have highlighted the existence of muscarinic receptors on inflammatory cells and we have explored the possibility that tiotropium bromide might also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 32 publications
(50 reference statements)
5
65
0
5
Order By: Relevance
“…However, in all cells studied to date, M 2 receptor mRNA was by far the most prominent transcript. In this regard, previous observations on phLFbs and MRC-5 cells [14] were confirmed in the present study in a larger series of experiments and extended to HEL-299 cells (figs 1 and 2), also observed a predominant expression of mRNA encoding the M 2 subtype [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…However, in all cells studied to date, M 2 receptor mRNA was by far the most prominent transcript. In this regard, previous observations on phLFbs and MRC-5 cells [14] were confirmed in the present study in a larger series of experiments and extended to HEL-299 cells (figs 1 and 2), also observed a predominant expression of mRNA encoding the M 2 subtype [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…We found a predominance of M2 and M3 muscarinic subtypes, with low amounts of M1 receptors. A similar pattern of expression was described for cultured respiratory epithelial cells [5,26]. In this sense, we found that siRNA specific for siRNA-M3 and the M3 antagonist pFHHSid attenuated the MUC5AC response to carbachol and CSE, while siRNA-M2 and the M2 antagonist methoctramine were without significant effects.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study showed that acetylcholine induces the release of neutrophil chemoattractants such as leukotriene B 4 from sputum cells of COPD patients [6]. These results are consistent with studies demonstrating that alveolar macrophages exhibit neutrophil, eosinophil and monocyte chemotactic activities in response to acetylcholine [7,8] and suggest that acetylcholine is a paracrine and/or autocrine mediator that regulates inflammatory processes.…”
supporting
confidence: 80%